2008
DOI: 10.1021/cg0704044
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Structure Analysis of Nanocrystalline Boehmite AlO(OH)

Abstract: Nanocrystalline n-AlO(OH) (Disperal P2 ® of Sasol) was investigated by means of the atomic pair distribution function (PDF). The PDF is derived from powder diffraction data, an ideally resolved PDF is obtained from a synchrotron source which provides a large maximal scattering vector length Q max > 300 nm -1 . Here, however, we were able to reveal atomic structure details of the ~ 4 nm particles from in-house diffraction data (Q max = 130 nm -1 ): PDF least squares model refinements show that n-AlO(OH) is of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 9 publications
4
47
0
6
Order By: Relevance
“…19 Yawata reported on recovering lithium ions from hot spring water using H 2 TiO 3 , obtained from Li 2 TiO 3 by an ion exchange reaction. 20 Recently, we showed that all three MO(OH) 2 (M = Ti, Zr, Hf ) oxyhydroxides can be synthesised in solid form by an ion exchange reaction in aqueous acetic acid solution from Li 2 MO 3 (M = Ti, Zr, Hf ) precursors. 19,[21][22][23] It is worth mentioning that the precursors in ref.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…19 Yawata reported on recovering lithium ions from hot spring water using H 2 TiO 3 , obtained from Li 2 TiO 3 by an ion exchange reaction. 20 Recently, we showed that all three MO(OH) 2 (M = Ti, Zr, Hf ) oxyhydroxides can be synthesised in solid form by an ion exchange reaction in aqueous acetic acid solution from Li 2 MO 3 (M = Ti, Zr, Hf ) precursors. 19,[21][22][23] It is worth mentioning that the precursors in ref.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] have been obtained by standard solid-state synthesis at temperatures 600-700°C, 19,21 which are significantly lower than the temperatures used during the solid-state synthesis of the above-mentioned lithium salts. [24][25][26][27][28][29][30] In the case of TiO(OH) 2 we showed that decreasing the synthesis temperature is crucial for obtaining oxyhydroxides. Indeed, only precursors annealed at low temperatures allow the complete exchange of Li + by H + (the extent of exchange of lithium by protons in Li 2 TiO 3 obtained at 800-1000°C was found to be less than 50%).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations